Just out of reach: how visual framing and hegemonic ideologies marginalize women in film - Giesenhagen, Julia, author; Tham, Samuel, advisor; Carvalho, Pedro, committee member (Colorado State University. Libraries, 2025)
In a historically male dominated industry, entertainment has seen limited representation of women in leading roles. When looking into the awards season, there are significant discrepancies between the reputation of female and male directors, leaving more success to male talent. With only 3 women ever winning the distinction of best director over 90+ years of the Academy Awards, there is growing concern over the validity of awards shows. With a thorough analysis of the industry utilizing visual framing methods and hegemonic ideologies, it is revealed that women have significantly less success due to perceptions adopted by audiences and the subjective biases held by the awards members.
University Honors Program
Journalism and Media Communications
Keywords: Barbie; gender marginalization; hegemony; visual framing